2018
DOI: 10.1111/jiec.12829
|View full text |Cite
|
Sign up to set email alerts
|

Towards Productive Cities: Environmental Assessment of the Food‐Energy‐Water Nexus of the Urban Roof Mosaic

Abstract: Summary Cities are rapidly growing and need to look for ways to optimize resource consumption. Metropolises are especially vulnerable in three main systems, often referred to as the FEW (i.e., food, energy, and water) nexus. In this context, urban rooftops are underutilized areas that might be used for the production of these resources. We developed the Roof Mosaic approach, which combines life cycle assessment with two rooftop guidelines, to analyze the technical feasibility and environmental implications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…We found that the fraction of biomass generated in i-RTG is similar in composition (stems, branches and leaves) to the classification of "bio-waste" from parks and gardens that are part of municipal waste (European Council, 2008). Based on the above considering the great potential for the implementation of food production systems on rooftops (Safayet et al, 2018;Toboso-Chavero et al, 2019) and according to the growth projection for green roofs in Barcelona (Barcelona, 2017), an increase of 20% of this type of waste was calculated by 2030 within the city.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the fraction of biomass generated in i-RTG is similar in composition (stems, branches and leaves) to the classification of "bio-waste" from parks and gardens that are part of municipal waste (European Council, 2008). Based on the above considering the great potential for the implementation of food production systems on rooftops (Safayet et al, 2018;Toboso-Chavero et al, 2019) and according to the growth projection for green roofs in Barcelona (Barcelona, 2017), an increase of 20% of this type of waste was calculated by 2030 within the city.…”
Section: Discussionmentioning
confidence: 99%
“…For 2019 the forecast of the covered area by green roofs was 5,431 m 2 and through the mosaic roof project, between 2020 and 2030 the creation of 22,000 m 2 will be promoted. The study by de Toboso-Chavero et al (2019) presents the "RoofMosaic" approach, which explores the concept of multiple uses on rooftops to create collective benefits at the local level and promote self-sufficiency in food, energy and water (FEW nexus). This by analyzing the technical, environmental and legal feasibility of the area.…”
Section: Circular Economy In Rtgmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their quick growth, cities present a specific vulnerability with regard to managing the food-energy-water (FEW) nexus and its elements, which illustrates the need for efforts to be made in terms of the optimization and use of natural resources (Toboso-Chavero et al, 2018). In this regard, cities have increased the pressure and exploitation levels imposed on the ecosystems, both at local and global scale, as they are responsible, in direct or indirect ways, for nearly 75 % of global energy consumption and 80% of greenhouse gas (GHG) emissions (Ash, Jasny, Roberts, Stone, & Sugden, 2008), exerting high impacts on levels of atmospheric pollution and on the rising demand for natural resources (Cerón-Palma, Sanyé-Mengual, Oliver-Solà, Montero, & Rieradevall, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dal Bo Zanon et al 2017), rooftop production(Sanjuan- Delmás et al 2018;Toboso-Chavero et al 2019;Salvador et al 2019), or urban aquaponics(Wu et al 2019).…”
mentioning
confidence: 99%